Risk factors for cervical lymph node metastasis of papillary thyroid cancer in elderly patients aged 65 and older - Zhang, Yu; Ji, Xiaoyu; Yang, Zhou; Wang, Yu (Frontiers in Endocrinology, 2024)
Objective: To assess the risk factors of cervical lymph node metastasis in elderly patients aged 65 years and older diagnosed with papillary thyroid cancer (PTC).In this retrospective analysis, we included a total of 328 elderly patients aged 65 years and older diagnosed with PTC. We thoroughly examined clinical features from these patients. Utilizing univariate and multivariate logistic regression analyses, we aimed to identify factors contributing to the risk of central and lateral lymph node metastasis (CLNM / LLNM) in this specific population of PTC patients aged 65 years and older.In the univariate analysis, CLNM was significantly associated with tumor size, multifocality, bilaterality, and microcalcification, while only tumor size ≥ 1cm (OR = 0.530, P = 0.019, 95% CI = 0.311 -0.900) and multifocality (OR = 0.291, P < 0.001, 95% CI = 0.148 -0.574) remained as risk factors in the multivariate analysis. LLNM was confirmed to be associated with male (OR = 0.454, P < 0.020, 95% CI = 0.233 -0.884), tumor size ≥ 1cm (OR = 0.471, P = 0.030, 95% CI = 0.239 -0.928), age ≥ 70 (OR = 0.489, P = 0.032, 95% CI = 0.254 -0.941), and microcalcification (OR = 0.384, P = 0.008, 95% CI = 0.189 -0.781) in the multivariate analysis. In elderly PTC patients with CLNM, male gender (OR = 2.857, P = 0.021, 95% CI = 1.170 -6.977), age ≥ 70 (OR = 2.952, P = 0.015, 95% CI = 1.234 -7.060), and bilaterality (OR = 3.125, P = 0.012, 95% CI = 1.284 -7.606) were closely associated with concomitant LLNM in both univariate and multivariate analyses.For elderly PTC patients aged 65 and older, tumor size ≥ 1cm and multifocality are significant risk factors for CLNM. Meanwhile, male, tumor size ≥ 1cm, age ≥ 70, and microcalcification are crucial predictors for LLNM. In patients already diagnosed with CLNM, male, age ≥ 70, and bilaterality increase the risk of LLNM.